Kimono exhibit catalog - Maxson, Mary Louise, author; Knoll, Diane Sparks, author (Colorado State University. Libraries, 1990)
Catalog of "Kimono" exhibit, running from March 29 to May 31, 1990 at the Gustafson Gallery. Catalog contains information of kimonos displayed in the exhibit.
Keywords: Fashion -- History; Fashion -- Exhibitions